PENERAPAN KOMBINASI MODEL PEMBELAJARAN KOOPERATIF TWO STAY TWO STRAY DENGAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS XI-IIS 6 SMA NEGERI 8 SURAKARTA TAHUN PELAJARAN 2015/2016 - Margaretha Puspita Arumsari; Mintasih Indriayu; Salman Alfarisy Totalia (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The objective of this research are to improve the economic learning outcomes in the  XI-IIS 6 grade of SMA Negeri 8 Surakarta  through the application of combination of the cooperative learning model between Two Stay Two Stray with Make A Match. This research used the Classroom Action Research (CAR). The study was conducted in two cycles, with each cycle consisted of planning, implementation, observation and reflection. The subjects were 28 students in the XI-IIS 6 grade of SMA Negeri 8 Surakarta in academic year 2015/2016. Data collection techniques are observation, test, documentation and  interview. The result  of research   can  conclution  that application  of combination of the cooperative learning model between two stay two stray with make a match can improve the ecconomic learning outcomes in the XI-IIS 6 grade of SMA Negeri 8 Surakarta in academic year 2015/2016. It proved from prior- action, cycle I and cycle II that the students learning outcomes is viewed  from increases every aspect. The proportion aspect cognitive of students learning outcomes passing are 42.86% in prior action, 67.86% in cycle I, and 85.71% in cycle II. Affective aspect of student learning outcomes were 42.85% in prior action, 78.58% in cycle I and 92.85% in cycle II. The psychomotor aspect of student learning outcomes were 0.00% in prior action, 57.14% in cycle I, and 85.71% in cycle II.